(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To compare low versus high implant density in decreasing Cobb angle in Lenke Type 1 Adolescent Idiopathic Scoliosis(AIS) treated with segmental spinal instrumentation and pedicle screws. Methods: This retrospective Cohort study was conducted at Department of Orthopedic and Spine Surgery, Ghurki Trust Teaching Hospital/ Lahore Medical and Dental College, Lahore. The medical records of patients between 15th June 2015 to 15th June 2019 who underwent segmental spinal instrumentation for Lenke type 1 adolescent idiopathic scoliosis were reviewed. Low implant density was defined as patients with pedicle screw density per fused segment of 60 %( ?1.2) or less while high density patients had more than 60 % (> 1.2) screw density. Radiographs were evaluated preoperatively for Cobb angle of main thoracic curve, sagittal and lumbar modifier. Postoperative evaluation included postoperative Cobb angle, percent Cobb angle decease, implant density and implant cost. Independent sample t-test, paired Sample t-test and Chi-square test of association were applied to compare preoperative and postoperative variables between two groups. P<0.05 was set as significant. Results: The total number of patients in our study was 66. Female patients were 47(71.2%) and male 19(28.7%). In low implant density group there were 25 patients including 17(68%) female and 8(32%) male. Mean pre-operative and post-operative Cobb angle was 62.60±130 (450-900) and 13.80±8.070 (0-250) respectively. Mean percent Cobb angle decrease, implant density and implant cost was 78.56±12.07% (50-100%), 1.11±0.083 (0.9-1.20) per fused segment and rupees 85248±13414.57 respectively. High implant density group included total 41 patients with 30(73.2%) females and 11(26.8%) males. Mean preoperative and postoperative Cobb angle was 65.240±16.160 (450-1000) and 13.290±8.180 (0-250) respectively. Mean percent Cobb angle decrease, implant density and implant cost was 79.85±12.85%(44-100%), 1.499±0.09 (1.29-1.65) per fused segment and rupees 93658.53±10589.64 respectively. Comparison between the two groups showed no significant difference in percent Cobb angle decrease (P=0.868). However implant cost was significantly reduced in low implant density group (p=0.000) Conclusion: Correction of Cobb angle was not significantly influenced by metal density and henceforth low implant density can be used to obtain excellent correction in Lenke type 1 idiopathic Scoliosis(AIS) treated with segmental spinal instrumentation and pedicle screws. Keywords: Adolescent Idiopathic Scoliosis, Cobb angle, Lenke type 1, Pedicle screw, Segmental spinal instrumentation.